DAYA TARIK JURNALISTIK, PERS, BERITA DAN PERBEDAAN PERAN DALAM NEWS CASTING - Restendy, Mochammad Sinung (Jurnal al Hikmah, 2016)
Journalism, Press and News have tremendous appeal and can not be separated in their daily lives so that the process of extracting container news in the mass media, both print and electronic delivery of great need that audience or news lovers do not feel bored or lazy to read. The lack of understanding of journalism, the press and the news caused appeal reduced in journalism, Press and news. One of the actors is also media professionals and the public are less competent in understanding the news, news writing and in the context of its delivery. Based on the background of the problems in the above article the author makes a conceptual